ショウワ キチ シュウヘン デ オコナッタ コショウ チョウサ ヨホウ 1981 1985 ネン - 村山, 治太; ムラヤマ, ハルタ; 日高, 秀夫; ヒダカ, ヒデオ; 吉田, 栄夫; ヨシダ, ヨシオ; Murayama, Haruta; Hidaka, Hideo; Yoshida, Yoshio (1988)
P(論文) 環境モニタリング観測計画の一環として行われた, 南極リュツォ・ホルム湾東岸露岩地帯の湖沼調査の結果のうち, 湖の水温垂直分布について, 第26次観測隊による観測を中心に, 第22次観測隊の観測結果を加えて資料として示し, それ以前の若干の結果を併せて, その季節変動の特徴や年ごとの変動の一端を予察的に記述した。塩湖はそれぞれ特徴のある温度分布を示し, それらはいずれも大まかに季節的変動の大きい上部層と小さい下部層の二層構造を示し, 化学成層に対応している。淡水湖は氷に覆われている間, 典型的な逆列成層を示すことが確かめられた。また, 従来調査が行われなかったリュツォ・ホルム湾南部のルンドボークスヘッタおよびベルオッデンの湖水温, 主化学成分の調査結果を示した。これらの湖は氷床に接していてその涵養を受けており, 湖水の塩分濃度は極めて低く, 1985/1986年にはこの地域の淡水湖としては極めて低温の湖であった。ルンドボークスヘッタの湖は過去の観察, 空中写真によると, 夏期の湖氷の融解の程度の年ごとの変動が大きく, 局地的な気候条件をよく反映することも指摘できる。 The characteristics of vertical water temperature distributions of several lakes which have been studied as part of the "monitoring of the environmental change project" in the Lutzow-Holm Bay region are preliminarily reported, based mainly on the results obtained by the 26th Japanese Antarctic Research Expedition (JARE-26) in 1985/1986 and in part by JARE-22 in 1981,together with some other data. Selected lakes consist of saline and freshwater ones. Each saline lake has its characteristic temperature distributions, and seems to have two-layer structure which consists of the upper layer undergoing large seasonal fluctuations and the lower layer having rather stable temperature distributions. This structure corresponds to remarkable chemical stratification. The pattern of temperature distribution of each lake seems to have differed little for considerable years, but the absolute temperature value changes slightly from year to year. Freshwater lakes show typical inverse stratification when lakes are covered with an ice layer in winter, and fluctuation from year to year is very small. In addition, general features of two newly investigated lakes are reported. They are situated in ice-free areas in the southern part of the eastern coast of Lutzow-Holm Bay, adjoining the ice sheet. Their waters show very low concentration of dissolved salts. departmental bulletin paper